Specific fitness training and testing in competitive sports - Müller, E.; Benko, U.; Raschner, C.; Schwameder, H. (Medicine & Science in Sports & Exercise, 2000)
Improvements of athletic capacity in high-performance sport are mainly achieved through an increase of the quality of training. In physical preparation, the quality of training can be improved by developing highly specific means of training. The aim of this paper is to present three examples of how highly specific means of fitness training of world class athletes can be developed. The first example presents a test profile of specific motor abilities of top class tennis players, the second one deals with the improvement of specific strength training methods for ski jumpers, and the third deals with the development of specific training devices of Alpine ski racers.